Inter-gender murder in NSW, 1901–1955: Reconsidering the laws of the fraternity - Strange, Carolyn (Journal of criminology, 2021)
Contemporary studies that focus on intimate homicide assume that patterns of policing, prosecution and punishment were uniformly disadvantageous to women before feminist activists intervened in the 1970s. This article tests that assumption by drawing on the Prosecution Project’s digitisation of Australian criminal trial records. Using this resource, we selected all prosecutions (n = 314) of men for murders of women and of women for murders of men in New South Wales, from Federation (1901) to 1955, the year the state abolished the death penalty. By coding victim–offender relationships and analysing them in relation to case outcomes, we found that men were far more likely than women to be convicted of murder, including seven men executed for intimate femicides. By contrast, women were more likely than men to be acquitted outright, rather than plead guilty to manslaughter of male intimates, a trend that feminist research has identified recently. This research provides new findings of use to critical appraisals of the charging and sentencing reforms that were meant to remedy ‘the laws of the fraternity’.